Emotion Analysis and Performance Perdiction Using Cluster Based LDA - Devi, Kajal; Kaur, Harjinder (International Journal of Computer Sciences and Engineering, 2021)
Kajal Devi, Harjinder Kaur, for a productive life, Marketing plays a critical role to fill individual life with value and excellence. Marketing is compulsory to provide things that individuals partake in to compete in the modern world. Predicting the academic performance of the Business is the most successive research in this era. A different set of approaches and methods are incorporated to increase Business performance. However, this is a challenging task due to the wrong course selection. In this paper, we have used the Cluster-based Linear Discriminant Analysis (CLDA) and Artificial Neural Network (ANN) based approaches for the prediction and classification of Business performance. The proposed study will provide the prospective business with the motivational comments and the video recommendations by which Business can choose the right subject and the comments will facilitate the Business with the insight reasons of dropout opted by other Business for this course. The outcomes of this study will help in the reduction of the number of dropouts. The Business will be able to choose an appropriate course for performance enhancement and carrier excel.